The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1993
DOI: 10.1007/bf00302115
|View full text |Cite
|
Sign up to set email alerts
|

The thyroid and photoperiodic control of seasonal reproduction in American tree sparrows (Spizella arborea)

Abstract: To explore the role of the thyroid gland in the control of seasonal reproduction in obligately photoperiodic American tree sparrows (Spizella arborea), the effects of (1) thyroxine administered in drinking water to thyroid-intact photosensitive or photorefractory birds, and (2) radiothyroidectomy before and after photostimulation and during photorefractoriness were examined. Chronic administration of pharmacological doses of thyroxine induced testicular growth and usually regression in initially photosensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Beyond anuran metamorphosis, thyroid hormone has been implicated in a wide range of important biological processes in organisms that lack an available genetic approach. These include direct and indirect development of amphibians and fish (28 -31), the control of photoperiodism in seasonally breeding birds (32), and smoltification of salmonids (33,34), all of which can be explored in more mechanistic detail using NH-3. Finally, our results clearly demonstrate the degree of structural and functional relatedness between the mammalian and amphibian TRs and further underscore the usefulness of the amphibian model for identifying biologically active nuclear receptor ligands.…”
Section: Co-activator Recruitment By the Trs Is Inhibited By Nh-3-mentioning
confidence: 99%
“…Beyond anuran metamorphosis, thyroid hormone has been implicated in a wide range of important biological processes in organisms that lack an available genetic approach. These include direct and indirect development of amphibians and fish (28 -31), the control of photoperiodism in seasonally breeding birds (32), and smoltification of salmonids (33,34), all of which can be explored in more mechanistic detail using NH-3. Finally, our results clearly demonstrate the degree of structural and functional relatedness between the mammalian and amphibian TRs and further underscore the usefulness of the amphibian model for identifying biologically active nuclear receptor ligands.…”
Section: Co-activator Recruitment By the Trs Is Inhibited By Nh-3-mentioning
confidence: 99%
“…In addition, each of the 18 primary flight feathers was assigned a molt score using Newton's [25] scale of 0 (old) to 5 (new). Because neither testicular growth nor molt occurs in photosensitive tree sparrows held on short days [14,18], testis lengths and molt scores recorded at Week -1 reflect testicular condition and molt status at Week 0, at which time one group of males (short-day controls) was retained on 8L: 16D and seven groups (including long-day controls) were moved to 20L:4D. One day, 4 days, 1 wk, 2 wk, 3 wk, and 4 wk later, a separate group of males was evaluated for testis length, scored for molt, and returned to 8L:16D for 7 -n wk (i.e., for a period ranging from 6.86 wk [after 1 day on 20L:4D] to 3 wk [after 4 wk on 20L:4D]); longday controls remained on 20L:4D for 7 wk.…”
Section: Experimental Designmentioning
confidence: 99%
“…Our studies on obligately photoperiodic American tree sparrows (Spizella arborea) lead us to conclude that THs and long days interact to program males for the vernal component of seasonality, as well as the autumnal component [12,[14][15][16][17][18]. By performing thyroidectomy (THX) before, at, or after the onset of photostimulation, we have demonstrated that programming for testicular growth occurs during the first week of photostimulation [16,18] and is independent of programming for photorefractoriness and postnuptial molt, which occurs between Weeks 1 and 3 [15,16,18].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Photorefractoriness, "a reversible state of unresponsiveness to gonado-stimulatory daylengths," initiates and then terminates breeding in photoperiodic species of birds (32). Preventing migrating species from breeding out of season is especially critical for their survival.…”
Section: Birdsmentioning
confidence: 99%